Mental health symptoms and sleep quality of asymptomatic/mild SARS‐CoV‐2 infected individuals during the Omicron wave of the COVID‐19 pandemic in Shanghai China. Issue 12 (3rd November 2022) - Hou, Zhenghua; Huang, Yingzi; Ma, Shaolei; Feng, Hui; Fu, Cuiping; Li, Han; Yuan, Yuexing; Yuan, Yonggui
Abstract: Objective: To investigate mental health symptoms (anxiety, depression, and sleep status) and their associated factors among people infected with the SARS‐CoV‐2 omicron variant during the quarantine period in Shanghai. Methods: To investigate the mental health symptoms among participants with SARS‐CoV‐2 omicron infection, an anonymous online survey questionnaire was used. The survey panel included the 9‐item Patient Health Questionnaire‐9 (PHQ‐9), 7‐item Generalized Anxiety Disorder Scale (GAD‐7), Pittsburgh Sleep Quality Index (PSQI), and 22‐item Ruminative Responses Scale (RRS). Group comparisons and correlation analyses were employed to explore the epidemiological characteristics of patients and factors related to depression and anxiety symptoms. Results: A total of 960 participants completed the survey. Of the total respondents, 583 participants (60.7%) were male, and the mean (SD) age was 34.33 (9.21) years (95% CI: 33.74–34.91). The prevalence of depressive and anxiety symptoms among the participants was 13.7% ( n  = 151, 95% CI: 11.6%–15.7%) and 8.6% ( n  = 90, 95% CI: 6.9%–10.3%), respectively. Age‐stratified analysis showed that the prevalence of anxiety among the 36‐ to 45‐year‐old group (12.9%; n  = 35, 8.9%–16.9%) was significantly higher than that of the 18‐ to 15‐year‐old group (7.4%; n  = 42, 5.3%–9.6%, p  = .011). Spearman's correlation analyses showed that rumination (assessed by the RRS) was significantly and positively correlated with depression (rho = .706, p  < .001) and anxiety symptoms (rho = .758, p  < .001). Conclusion: The results suggest that female and middle‐aged populations manifest higher susceptibility to mental health distress during the current Omicron wave of the COVID‐19 pandemic. Population‐specific psychological crisis intervention is warranted to improve the quality of epidemic prevention methods and to promote the mental well‐being of the public.